Poetry - Strachan, John (John R.), 1961- (Edinburgh University Press, 2011)
Quickly equips you with the strategies you need to deepen your engagement with individual poems. New for this edition:. End-of-chapter exercises and follow-up research tasks New readings of modern women's poetry Section on How to Write Poetry with exercises Suggestions for further reading - both books and websites Based on their extensive teaching experience, the authors provide a lively route map through the main aspects of poetry such as sound effects, rhythm and metre, the typographic display of poems on the page and the language of poetry using practical examples throughout. Key Features. Packed full of examples, from the work of Shakespeare to Edwin Morgan and from Sylvia Plath to John Agard Detailed index of poets, works, terms, forms & concepts Full glossary of poetic terms, from acatalectic to wrenched accent, with cross-references and page references of examples Praise for the first edition:. 'Wide-ranging, provocative, and thorough, Strachan and Terry provide the student with all the tools necessary for the study of poetry. I can think of no other volume that offers the reader so much in so few pages. This is the text of choice for all students and teachers of the subject.' Duncan Wu, University of Glasgow